2016
DOI: 10.1177/0956462415616038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent bacterial vaginosis infection – a risk factor for incident sexually transmitted infections in women in Durban, South Africa

Abstract: The association between bacterial vaginosis (BV) and incident sexually transmitted infections (STIs) in a cohort of high-risk women from Durban, South Africa was investigated in this study. We undertook a secondary analysis of the Methods for Improving Reproductive Health in Africa trial that assessed effectiveness of the latex diaphragm and lubricant gel on HIV prevention among women. During study visits, urine specimens were collected for testing for Neisseria gonorrhoeae, Chlamydia trachomatis and Trichomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 16 publications
1
58
0
3
Order By: Relevance
“…Women with BV had an almost 3-fold higher risk of infection with a curable STIs than women without BV, comparable to other studies [4, 33]. It might be advisable to better document the presence of BV.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Women with BV had an almost 3-fold higher risk of infection with a curable STIs than women without BV, comparable to other studies [4, 33]. It might be advisable to better document the presence of BV.…”
Section: Discussionsupporting
confidence: 79%
“…trachomatis and N . gonorrhoeae [3, 4], is highly prevalent [5]. These curable STIs and BV have been associated with a number of adverse pregnancy outcomes such as spontaneous abortion, ectopic pregnancy, preterm delivery, low birth weight, stillbirth, postpartum sepsis, and congenital infection [6].…”
Section: Introductionmentioning
confidence: 99%
“…BV in pregnancy is clinically significant because of its association with pre-term labor and delivery, pre-mature, pre-labor rupture of membranes, spontaneous miscarriage, and infections post-delivery [3][4][5][6]. BV may also pose a risk for the acquisition of sexually transmitted infections (STIs) such as HIV, N. gonorrhoeae, C. trachomatis, and HSV-2 that are independently associated with preterm delivery if untreated [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…; Abbai et al . ). The connection between bacterial vaginosis and chlamydia infection is not clear, but one of the possibilities is the increased indole production of the bacterial vaginosis‐related bacteria (Aiyar et al .…”
Section: Introductionmentioning
confidence: 97%
“…Bacterial vaginosis is a state where the normal lactobacillus flora of the vagina is disappearing and is replaced by a polybacterial flora. Several studies showed that bacterial vaginosis is a significant risk factor of acquiring STIs including chlamydial STIs with a relative risk of 2Á0-3Á4 (Wiesenfeld et al 2003;Aghaizu et al 2014;Abbai et al 2015). The connection between bacterial vaginosis and chlamydia infection is not clear, but one of the possibilities is the increased indole production of the bacterial vaginosis-related bacteria (Aiyar et al 2014).…”
Section: Introductionmentioning
confidence: 99%